2013
DOI: 10.4103/2279-042x.128144
|View full text |Cite
|
Sign up to set email alerts
|

Social risk factors and outcome analysis of poisoning in an Iranian referral medical center: A toxico-epidemiological approach

Abstract: Objective:Suicide is the second major reason of death in the age range of 15-24 and is the eighth reason for overall death of adults. Because of high accessibility of people to different medications in our society, one of the easiest ways for suicide is intentional self-poisoning with medications. Therefore, the aim of this study was to determine the rate of suicide with respect to influencing social factors on patients with intentional self-poisoning.Methods:This was an analytic-descriptive prospective study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In a study of 414 patients in Gorgan, 82.6% of the cases were poisoned by pharmaceutical drugs ( 29 ). In the second geographical zone, in two studies in Isfahan from 2015 and 2013, pharmaceutical drugs, specifically psychiatric pharmaceutical drugs, were the leading cause of poisoning ( 30 , 31 ). Another study of 266 poisoned patients, in Shiraz, found that drug poisoning was the most common type of poisoning (68%) ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 414 patients in Gorgan, 82.6% of the cases were poisoned by pharmaceutical drugs ( 29 ). In the second geographical zone, in two studies in Isfahan from 2015 and 2013, pharmaceutical drugs, specifically psychiatric pharmaceutical drugs, were the leading cause of poisoning ( 30 , 31 ). Another study of 266 poisoned patients, in Shiraz, found that drug poisoning was the most common type of poisoning (68%) ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Sari, from 2,057 poisoned patients, organophosphate insecticides and carbamates were the third most common cause of poisoning, after pharmaceutical drugs and opioids ( 6 ). In the second zone of Iran, one study of 400 poisoned patients in Isfahan reported organophosphates (2.75%) as the third most common source of poisoning ( 30 ). In a study of 786 poisoned patients from vulnerable social stratum in Isfahan, 4.4% were due to pesticides, which was again the third most common cause of poisoning ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[678910] Depression on the top causes of suicide has been evaluated in many articles. Many predisposing factors have been mentioned for depression which may have also a role in suicide.…”
Section: Introductionmentioning
confidence: 99%
“…In our clinical setting (Noor and Ali Asghar [PBUH] University Hospital, Isfahan, Iran), carbamazepine poisoning is one of the three most important causes of status epilepticus. [ 19 ] With regard to the serious complications of frequent seizure episodes and status epilepticus after carbamazepine poisoning (e.g., hypoxic brain damages in status epilepticus, sudden death with arrhythmia, rhabdomyolysis and aspiration pneumonia),[ 20 21 ] the evaluation of the associated risk factors for this type of seizure seems to be important. Therefore, this study was performed in order to increase the present knowledge about the frequency of seizure in carbamazepine poisoned patients and to define the important risk factors related to the outcomes of therapy, as well as the prognosis of these patients.…”
Section: Introductionmentioning
confidence: 99%